Analisis Prediksi Kebangkrutan Dengan Menggunakan Metode Altman Z-Score Pada PT. Wijaya Karya (Persero) Tbk - Irfan Ardiwinarta; Nazmah Auliani Dewi; Nardi Sunardi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research aims to determine the level of company bankruptcy using the Altman Z-Score model. Company PT. Wijaya Karya (Persero) Tbk from 2013 to 2022. This research uses secondary data in the form of quantitative data. The data source used in this research comes from the financial reports of the company PT. Wijaya Karya (Persero) Tbk which is listed on the Indonesia Stock Exchange (BEI) for the period 2013 - 2022. The Altman Z-Score method uses five variables, namely: Working capital/total assets (X1), Retained earnings/total assets (X2), Profit before interest and taxes/total assets (X3), Market value of equity/book value of debt (X4), and Sales/total assets (X5). The results of this research indicate that the Altman Z-Score model can be implemented in detecting the possibility of bankruptcy in PT companies. Wijaya Karya (Persero) Tbk. The results of the analysis show that the company PT. Wijaya Karya (Persero) Tbk is predicted to experience bankruptcy in 2019 - 2022. This is indicated by a Z-Score value below 1.8, which means very large financial difficulties and high risk. in 2013 - 2018, those who were predicted to be prone to bankruptcy were marked with a Z-Score value of 1.81 < Z-Score < 2.99.